PENGARUH PEMBERIAN PUPUK ORGANIK CAIR (POC) TOP G2 DENGAN DOSIS YANG BERBEDA TERHADAP PERTUMBUHAN KENTANG (SOLANUM TUBEROSUM L.) DI GREEN HOUSE FMIPA UPG 1945 NTT - Lendi Nomleni; Nur Aini Bunyani; Maya F, Roman; Nardi Matias Leo (Adisam Publisher, 2025)
The research was conducted at the Green House of FMIPA, Universitas Persatuan Guru 1945, Nusa Tenggara Timor for 3 months, namely February to May 2025. Research purposes To determine the effect of Top G2 liquid organic fertilizer on the growth of potato plants (Solanum tuberosum L.) To determine the best dosage of TOP G2 liquid organic fertilizer on the growth of potato plants (Solanum tuberosum L.) This study used a completely randomized experimental design (CRD) with the treatment repeated 5 times so that 25 experimental units were obtained. P0: Control (no treatment), P1: 5 ml / 1 liter of water, P2: 10 ml / 1 liter of water, P3: 15 ml / 1 liter of water, P4: 20 ml / 1 liter of water. In this study, 5 treatments were carried out and repeated 5 times so that 25 experimental units were obtained. The results of this study indicate that the administration of liquid organic fertilizer (POC) Top G2 with a dose of 20 ml / 1 liter of water gave the highest results in potato plant height (22.14 cm), number of leaves (11.74 strands), and number of stems (5.02).